Pertobatan Akademis - Hondi Panjaitan (Bina Nusantara University, 2013)
The biggest difficulty of humans cannot change or advance the quality of life is an unwillingness to change their errors and shortcomings and to repent from it. There is also willing to change but they do not change just because no action and do not really do it. There are also people who have already known that it is true, accurate, should be performed and corresponding to the norms, but still they live in sin and self-interest to ignore the interests of others. Even worse is evil (sin) is often covered in hypocrisy behind beautiful, sweet, gentle, and courteous words to make people mesmerized/hypnotized. In the case of real repentance, it should demand a match between words and actions. If there is repentance, there is a change and peace. Therefore, humans must sincerely repent and strive for it.